GPS and BDS combined PPP model with inter-system differenced observations. Issue 1 (1st January 2020) - Tu, Rui; Hong, Ju; Zhang, Rui; Han, Junqiang; Fan, Lihong; Zhang, Pengfei; Liu, Jinhai; Lu, Xiaochun
Abstract: This study proposes a combined precise point positioning (PPP) model, called the inter-system differenced PPP model, in which it formed the satellite-differenced observation between different satellite systems. Compared with the traditional combined PPP model, the inter-system differenced PPP model has the following characteristics: (1) The satellite difference between various systems can eliminate the receiver clock bias parameter, it enhances the strength of the PPP model. (2) Inter-satellite differences can eliminate some common model errors and reduce the impact of observation errors. (3) The system time difference can be calculated directly to provide the basis for time offset monitoring. In order to verify the positioning results of the inter-system differenced model, static PPP and dynamic PPP experiments were carried out to test the positioning accuracy and convergence time, and the results were compared with those of the traditional combination PPP model. In addition, the offset characteristics introduced by the inter-system differenced model were analysed, and the optimal estimation strategy was determined by dynamic PPP tests. Preliminary results are as follows: (1) For inter-system differenced static PPP, the convergence time of stations is less than 20 min. The standard deviation (STD) of the position bias for the East (E), North (N), and Up (U) components are better than 2.5 cm, 1.0 cm and 3.0 cm, respectively, and the corresponding root mean square deviation (RMS) are better than 3.0 cm, 1.5 cm and 6.0 cm, respectively. Compared with the traditional combined PPP model, the average convergence time of the inter-system differenced model is nearly the same, but its overall positioning accuracy is better. (2) For the inter-system differenced dynamic PPP model, the convergence time of stations is better than 30 min. The STD of the position bias for the E, N, and U components is better than 3.0 cm, 2.0 cm and 4.5 cm respectively, and the RMS is better than 4.0 cm, 2.5 cm and 7.0 cm respectively. Compared with the traditional combined PPP model, the convergence of the inter-system differenced model is slightly better, and the positioning accuracy does not differ significantly. Moreover, the inter-system differenced model is much better than the traditional model when fewer satellites are available. (3) The offset between GPS and BDS corresponding with the precise products of GFZ is related to the type of receiver, and the daily standard of offset is less than 0.5 ns. In addition, we determined optimum process noise of the offset parameter to be a 10 - 3 / 3 ( m 2 / s ) random walk after comparing several options.